What is e-health? - Sami Gomaa Al Anazi; Salem M Al Mutairi; Barrak Mohammed Aldawsari; Omar Abdulaziz Alghamdi; Norah Mohammed Aldossary; Muna Khalaf Alanazi; Dalia Hamoud Alonazi; Noha Fahmi Bawayan; Mohammed Sultan Mohammed Al Otaibi (Zenodo, 2023)
Abstract: E-health can be defined as a set of technologies, applied using the Internet, where healthcare services are delivered to improve quality of life and facilitate healthcare delivery. Due to the lack of similar studies on the subject, this analysis uses a systematic literature review of articles published between 2014 and 2019 to identify the most commonly used eHealth practices worldwide, as well as the main services offered, the diseases treated and associated technologies, who support in eHealth practices. One of the main results was the identification of the four most used practices (mHealth or mobile health; telemedicine or telemedicine; technology; and others) and the most used technologies related to e-health (IoT, cloud computing, big data, security and systems). Keywords: E-health, technologies, healthcare services. Title: What is e-health? Author: Sami Gomaa Al Anazi, Salem M Al Mutairi, Barrak Mohammed Aldawsari, Omar Abdulaziz Alghamdi, Norah Mohammed Aldossary, Muna Khalaf Alanazi, Dalia Hamoud Alonazi, Noha Fahmi Bawayan, Mohammed Sultan Mohammed Al Otaibi International Journal of Life Sciences Research ISSN 2348-313X (Print), ISSN 2348-3148 (online) Vol. 11, Issue 1, January 2023 - March 2023 Page No: 15-17 Research Publish Journals Website: www.researchpublish.com Published Date: 28-January-2023 DOI: https://doi.org/10.5281/zenodo.7578796 Paper Download Link (Source) https://www.researchpublish.com/papers/what-is-e-health International Journal of Life Sciences Research, ISSN 2348-313X (Print), ISSN 2348-3148 (online), Research Publish Journals, Website: www.researchpublish.com